Frequency of Vitamin D Deficiency in Patients with Bacterial Vaginosis during First Trimester of Pregnancy: Vitamin D Deficiency in Patients with Bacterial Vaginosis - Baloach, Shazia; Arshad, Maria; Parveen, Tahira; Seher, Aisha; Sohail, Farzana; Malhan, Asifa; Fazal, Adnan (Pakistan Journal of Health Sciences, 2023)
Bacterial vaginosis (BV) is an infection mainly results due to overabundance of germs. Because it affects a variety of immune system functions, it is crucial for BV. In order to timely assess, rationalize prospectively, and manage patients to combat vitamin D deficiency in bacterial vaginosis, this study planned to conduct on patients with bacterial vaginosis in relation to vitamin D deficiency, evaluate the magnitude, and generate local data. Objective: To determine the frequency of vitamin D deficiency in patients with bacterial vaginosis during first trimester of pregnancy. Methods: This cross-sectional study was conducted at Gynecology and Obstetrics department of Shaikh Zaid Women Hospital, SMBBMU Larkana from 10-September-2018 to 10-march-2019. A total of 192 pregnant women of first trimester with bacterial vaginosis were selected for this study. All the pregnant ladies with bacterial vaginosis were recruited and entered in the study and was screened for vitamin D deficiency. The data were collected on prepared proforma. Results: The age range from 25 to 35 years with a mean of 29.8±6.5 years, with mean gestational age of 8.09 ±2.29 weeks. Frequency of vitamin D deficiency was 47.4% in women with bacterial vaginosis in their first trimester. Conclusions: Findings of our study suggest association between vitamin D insufficiencies with BV during first trimester of pregnancy.